University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 3 - Section 3.6 - The Chain Rule - Exercises - Page 158: 36



Work Step by Step

$$y=(1+2x)e^{-2x}$$ The derivative of function $y$ is: $$y'=(1+2x)'e^{-2x}+(1+2x)(e^{-2x})'$$ $$y'=2e^{-2x}+(1+2x)e^{-2x}(-2x)'$$ $$y'=2e^{-2x}-2(1+2x)e^{-2x}$$ $$y'=2e^{-2x}(1-1-2x)$$ $$y'=2e^{-2x}(-2x)$$ $$y'=-4xe^{-2x}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.